Writing research papers : - Lester, James D. (Scott, Foresman, 1967)
Contents: This market-leading text provides students with step-by-step guidance through the research writing process, from selecting and narrowing a topic to formatting the finished document. Writing Research Papers backs up its instruction with the most complete array of samples of any writing guide of this nature. The text continues its extremely thorough and accurate coverage of citation styles for a wide variety of disciplines. The fourteenth edition maintains Lester's successful approach while bringing new writing and documentation updates to assist the student researcher in keeping pace with electronic sources.